Improving activity data for Tier 2 estimates of livestock emissions: Dealing with data gaps - Introduction and overview - Clark, Harry; Wollenberg, Eva Karoline (2018)
Expert workshop on Improving activity data for Tier 2 estimates of livestock emissions: Dealing with data gaps The Hauge, July 17-18, 2018 Introduction and overview